Matrix remodeling stimulates stromal autophagy, "fueling" cancer cell mitochondrial metabolism and metastasis - Castello-Cros, Remedios; Bonnuccelli, Gloria; Molchansky, Alex; Capozza, Franco; Witkiewicz, Agnieszka K.; Birbe, Ruth; Howell, Anthony; Pestell, Richard G.; Whitaker-Menezes, Diana; Sotgia, Federica; Lisanti, Michael P (Cell cycle (Georgetown, Tex.), 2011)
We have previously demonstrated that loss of stromal caveolin-1 (Cav-1) in cancer-associated fibroblasts is a strong and independent predictor of poor clinical outcome in human breast cancer patients. However, the signaling mechanism(s) by which Cav-1 downregulation leads to this tumor-promoting microenvironment are not well understood. To address this issue, we performed an unbiased comparative proteomic analysis of wild-type (WT) and Cav-1 -/- null mammary stromal fibroblasts (MSFs). Our results show that plasminogen activator inhibitor type 1 and type 2 (PAI-1 and PAI-2) expression is significantly increased in Cav-1 -/- MSFs. To establish a direct cause-effect relationship, we next generated immortalized human fibroblast lines stably overexpressing either PAI-1 or PAI-2. Importantly, PAI-1/2(+) fibroblasts promote the growth of MDA-MB-231 tumors (a human breast cancer cell line) in a murine xenograft model, without any increases in angiogenesis. Similarly, PAI-1/2(+) fibroblasts stimulate experimental metastasis of MDA-MB-231 cells using an in vivo lung colonization assay. Further mechanistic studies revealed that fibroblasts overexpressing PAI-1 or PAI-2 display increased autophagy ("self-eating") and are sufficient to induce mitochondrial biogenesis/activity in adjacent cancer cells, in co-culture experiments. In xenografts, PAI-1/2(+) fibroblasts significantly reduce the apoptosis of MDA-MB-231 tumor cells. The current study provides further support for the "Autophagic Tumor Stroma Model of Cancer" and identifies a novel "extracellular matrix"-based signaling mechanism, by which a loss of stromal Cav-1 generates a metastatic phenotype. Thus, the secretion and remodeling of extracellular matrix components (such as PAI-1/2) can directly regulate both (1) autophagy in stromal fibroblasts and (2) epithelial tumor cell mitochondrial metabolism.